Paranoid individuals with schizophrenia show greater social cognitive bias and worse social functioning than non-paranoid individuals with schizophrenia - Pinkham, Amy E. (Schizophr Res Cogn, 2016)
Paranoia is a common symptom of schizophrenia that may be related to how individuals process and respond to social stimuli. Previous investigations support a link between increased paranoia and greater social cognitive impairments, but these studies have been limited to single domains of social cognition, and no studies have examined how paranoia may influence functional outcome. Data from 147 individuals with schizophrenia were used to examine whether actively paranoid and non-paranoid individuals with schizophrenia differ in social cognition and functional outcomes. On measures assessing social cognitive bias, paranoid individuals endorsed more hostile and blaming attributions and identified more faces as untrustworthy; however, paranoid and non-paranoid individuals did not differ on emotion recognition and theory of mind tasks assessing social cognitive ability. Likewise, paranoid individuals showed greater impairments in real-world interpersonal relationships and social acceptability as compared to non-paranoid patients, but these differences did not extend to performance based tasks assessing functional capacity and social competence. These findings isolate specific social cognitive disparities between paranoid and non-paranoid subgroups and suggest that paranoia may exacerbate the social dysfunction that is commonly experienced by individuals with schizophrenia.